2019
DOI: 10.1186/s12888-018-2009-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dog-assisted therapy in adults with dementia: a systematic review and meta-analysis

Abstract: BackgroundDog-assisted therapy (DAT) is a non-pharmacological intervention based on the interaction between patients and dogs, which has been proposed to help adults with dementia. However, evidence to support it is lacking. Thus, we aim to evaluate the effects of DAT on this population and to assess the certainty of the evidence of the RCTs estimates.MethodsA systematic search was performed. We included randomized controlled trials (RCTs) and quasi-experimental (QE) controlled studies published up to March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 27 publications
5
52
0
Order By: Relevance
“…Two systematic reviews of systematic reviews (Abraha et al, 2017;Vilela, Pacheco, Latorraca, Pachito, & Riera, 2017) reveal that non-pharmacological interventions have positive effects on reducing BPSD, improving cognitive function, activities of daily living, and social interaction ability of patients with dementia. For apathy, there are several systematic reviews and meta-analyses (Brodaty & Burns, 2012;Fukushima et al, 2016;Goris, Ansel, & Schutte, 2016;Lane-Brown & Tate, 2009;Theleritis, Siarkos, Katirtzoglou, & Politis, 2016;Theleritis, Siarkos, Politis, Katirtzoglou, & Politis, 2018;Tsoi et al, 2018;Verkaik, Weert, & Francke, 2005;Zafra-Tanaka, Pacheco-Barrios, Tellez, & Taype-Rondan, 2019) of non-pharmacological interventions in patients with dementia. Nevertheless, these reviews involve diversified non-pharmacological interventions and lack evaluation of methodological quality and classification of evidence quality.…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews of systematic reviews (Abraha et al, 2017;Vilela, Pacheco, Latorraca, Pachito, & Riera, 2017) reveal that non-pharmacological interventions have positive effects on reducing BPSD, improving cognitive function, activities of daily living, and social interaction ability of patients with dementia. For apathy, there are several systematic reviews and meta-analyses (Brodaty & Burns, 2012;Fukushima et al, 2016;Goris, Ansel, & Schutte, 2016;Lane-Brown & Tate, 2009;Theleritis, Siarkos, Katirtzoglou, & Politis, 2016;Theleritis, Siarkos, Politis, Katirtzoglou, & Politis, 2018;Tsoi et al, 2018;Verkaik, Weert, & Francke, 2005;Zafra-Tanaka, Pacheco-Barrios, Tellez, & Taype-Rondan, 2019) of non-pharmacological interventions in patients with dementia. Nevertheless, these reviews involve diversified non-pharmacological interventions and lack evaluation of methodological quality and classification of evidence quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, the goals for DAT documented in this project are congruent with the current literature about effects of DAT across different patient groups and indications, 9,10,26 although not all studies show effects. 27 The documentation of the involved therapists after each session revealed that the most frequent goal realization was achieved in social, emotional, and psychological functioning. Having fun, establishing contact and communication, social and emotional competences, relaxation and attention were most successfully stimulated during DAT.…”
Section: Discussionmentioning
confidence: 99%
“…This tool considered three possible scores for each item from 0 to 2; 0 for not reported information, 1 for the information reported inadequately, and 2 for well-reported information. We considered for the overall risk of bias assessment that high risk of bias is indicated by scores less than 16 points, and low risk of bias indicated by 16 to 24 points, similar to previous studies 81,82 . Any disagreement was solved through discussion between the reviewers (KP-B and HZ).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%